SWOT Analysis of West Anatolia in the Context of History and Culture Tourism Potential - Tamer Baran; Serkan Bașol (Central European Journal of Geography and Sustainable Development, 2019)
The Anatolian peninsula is a unique geography which harbors almost all development stages of human history. As a piece of land that witnessed almost all the cultural, political, social and economic structures established by humanity including the first settlements built following the hunter-gatherer cultures, the start of agriculture, the foundation of the first central states following the principalities of the Bronze Age, the formation of empires following the Ancient Polis (city) States, Anatolia has a naturally rich archaeological heritage. In order to make use of this rich historical and cultural heritage in an efficient and sustainable way, especially in the tourism sector, one needs to determine the strengths and weaknesses of this potential. This study aims to make better use of the tourism potential of Western Anatolia by examining the strengths and weaknesses of the region with SWOT analysis method on Western Anatolia sample.